Standards of living and families : observation and analysis - Ekert-Jaffé, Olivia; Centre d'estudis demographics; Institut national d'études démographiques; Association européenne pour l'étude de la population
ill., couv. ill. en coul. EAPS = European association for population studies, INED = Institut national d'études démographiques